Pemenuhan Hak Dan Kewajiban Kesehatan dan Keselamatan Kerja Melalui Sistem Manajemen K3 Pada PT Antam Tbk - Widia , Firda; Afiyah, Salamatul (Jaanur Elbarik Indonesia, 2025)
This study analyzes the compliance of Occupational Safety and Health (OSH) implementation at PT Aneka Tambang Tbk, a state-owned mining company, using Government Regulation No. 50 of 2012 on the Occupational Safety and Health Management System (SMK3) as the analytical framework. Employing a descriptive qualitative approach through literature review, data were drawn from legislation, PT ANTAM’s annual and sustainability reports, and relevant scholarly works on mining OSH and Human Resource Management (HRM). The findings show that PT ANTAM demonstrates strong compliance with SMK3, reflected in clear OSH policies, structured risk control systems, continuous training, safety audits, and occupational health programs supporting workers’ well-being. The implementation contributes to fulfilling workers’ rights and highlights corporate responsibility from an HRM perspective. The study concludes that compliance analysis based on literature review is effective for assessing SMK3 implementation and serves as a foundation for strengthening safety culture in the mining sector